Experimental Studying the Belt Conveyor Roller Wear Dependence on the Intensity of Technological Dust Accumulation in Open Pit Mining - Kuanyshbayev, Adilzhan; Rozhkov, Alexander; Gorshkova, Nina; Nogayev, Kairosh (Communications - Scientific Letters of the University of Zilina, 2023)
The paper presents the research on revealing the causes of belt conveyors downtime at open-pit mining operations. By results of researches it is established that the reasons of the above mentioned problems are technological dust formed at crushing of mineral ore, further loading and unloading, and also at transporting by conveyors. Dense dust-air mixture settling on the rotating mechanisms of conveyors, gets into the bearing units and on the surfaces of friction gears, which accelerates the process of wear of parts several times.
Keywords: technological dust; rollers; wear of parts; friction; belt conveyor; bearings